Identification of Potential Waste Fluid Contamination with Geoelectric Method in Tebing Tinggi Subdistrict, West Tanjung Jabung Regency, Jambi - Salsabila Octara Sumaryanto; Nur Hidayat (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2022)
In the study area of Tebing Tinggi Subdistrict, Tanjung Jabung Barat Regency, Jambi Province, there are several companies engaged in the manufacturing, agriculture, and plantation industries. This company uses the Pengabuan river for transportation. Therefore, the study area has the potential to be contaminated by the waste fluid produced by the company. In this study, the geoelectric resistivity method was used because it is good for identifying potential contamination at the subsurface. The Wenner array was used because it is good in a study with shallow surfaces, so it is good at identifying contamination. Data processing is done by inversion process using Res2Dinv software to get 2D modeling and Voxler to get 3D modeling. Based on the 2D modeling, it is identified that the contamination is on lines 1, 2, and 4 with a resistivity range of ±0.059-2 Ωm. Also, in the study area, it is identified that there are alternating tuffaceous claystone, claystone, tuffaceous sandstone, sandstone, and shallow aquifer. Based on the 3D modeling, it is identified that there is a potential continuity of contamination between line 3 and line 4, which is at a distance of 0-8 m from line 4 to line 3.Keywords: Contamination, Geoelectric Resistivity Method, Res2Dinv, Voxler, Wenner Array